2011
DOI: 10.1073/pnas.1112722108
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to regulatory T cell-mediated suppression in rheumatoid arthritis can be bypassed by ectopic foxp3 expression in pathogenic synovial T cells

Abstract: Increasing evidence suggests that regulatory T cell (Treg) function is impaired in chronic inflammatory diseases such as rheumatoid arthritis (RA). Here we demonstrate that Tregs are unable to modulate the spontaneous production of TNF-α from RA synovial cells cultured from the diseased synovium site. Cytokine (IL-2, IL-6, TNF-α) activated T cells (Tck), cells we previously demonstrated to mimic the effector function of pathogenic RA synovial T cells, contained Tregs that survived and divided in this cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 56 publications
3
37
2
Order By: Relevance
“…Our data are consistent with previous studies demonstrating that CAR-engineered CD4 + T cells are capable of direct cytotoxicity and can drive specific cytolysis of target tumor cells (47)(48)(49). Beyond cancer, consistent gene transfer of FOXP3 into CD4 + cells is potent in inducing functional Tregs, which may be of relevance for novel therapeutic strategies in autoimmune and inflammatory diseases (3,4,50). In line with this idea, we demonstrated the feasibility of achieving continuous ectopic FOXP3 expression in CD4 + cells upon in vivo gene delivery by CD4-LV.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our data are consistent with previous studies demonstrating that CAR-engineered CD4 + T cells are capable of direct cytotoxicity and can drive specific cytolysis of target tumor cells (47)(48)(49). Beyond cancer, consistent gene transfer of FOXP3 into CD4 + cells is potent in inducing functional Tregs, which may be of relevance for novel therapeutic strategies in autoimmune and inflammatory diseases (3,4,50). In line with this idea, we demonstrated the feasibility of achieving continuous ectopic FOXP3 expression in CD4 + cells upon in vivo gene delivery by CD4-LV.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, recent studies have demonstrated that functional human regulatory T cells (Tregs) can be efficiently and consistently induced by ectopic FOXP3 expression mediated by lentiviral gene transfer in genetic autoimmune disease (3) and rheumatoid arthritis (4). Hence, CD4 + T cells are important target cells not only for understanding fundamental immunology but also for gene therapy and immunotherapy approaches.…”
Section: T He Cd4 + T Cells Are Key Players For Coordinating Immune Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression assays performed by two independent groups illustrated that Tregs from the SF of RA patients suppressed effector cell proliferation and reduced the concentrations of TNF and IFN-g produced in the supernatants (4,5), suggesting that Tregs in the synovial joint are in fact suppressive yet fail to constrain inflammation. On the other hand, Tregs from the peripheral blood of RA patients have been shown to be functionally impaired (6)(7)(8)(9).…”
Section: R Egulatory T Cells (Tregs)mentioning
confidence: 99%
“…Rather, their Tregs appear to be dysfunctional, with a loss of ability to suppress inflammatory cytokines such as TNF-α and interferon γ [81,82]. TNF-α, which is present in abundance in the rheumatoid joint, seems to be the major mediator of this down regulation [82][83][84][85]. This may occur through TNF-α inducing the release of PKCθ which blocks CTLA-4 binding [82].…”
Section: T Regulatory Cellsmentioning
confidence: 99%